Using Tobacco Leaves as Adsorbent for the Orange-G Dye Removal from its Aqueous Solutions - Rawaa Abbas Mohammed (Journal of Global Pharma Technology, 2016)
The removal of commercial orange G dye from its aqueous solution by adsorption on tobacco leaves (TL) was studied in respect to different factor that affected the adsorption process. These factors including the tobacco leaves does, period of orange G adsorption, pH, and initial orange G dye concentration .Different types of isotherm models were used to describe the orange G dye adsorption onto the tobacco leaves. The experimental results were compared using Langmuir, and frundlich adsorption isotherm, the constants for these two isotherm models was determined. The results fitted frundlich model with value of correlation coefficient equal to (0.981). The capacity of adsorption for the orange G dye was carried out using various kinetic models like pseudo first order-kinetic, pseudo second order –kinetic, Elovich, and inter particle diffusion model, the rate constants for these models were evaluated. The data suggested that tobacco leaves are suitable sorbent for the orange - G dye removal from its solution.Keywords: Adsorption, Orange G, Tobacco leaves.